An experimental test of the growth rate hypothesis as a predictive framework for microevolutionary adaptation. Issue 1 (23rd October 2022) - Lemmen, Kimberley D.; Zhou, Libin; Papakostas, Spiros; Declerck, Steven A. J.
Abstract: The growth rate hypothesis (GRH) posits that the relative body phosphorus content of an organism is positively related to somatic growth rate, as protein synthesis, which is necessary for growth, requires P‐rich rRNA. This hypothesis has strong support at the interspecific level. Here, we explore the use of the GRH to predict microevolutionary responses in consumer body stoichiometry. For this, we subjected populations of the rotifer Brachionus calyciflorus to selection for fast population growth rate (PGR) in P‐rich (HPF) and P‐poor (LPF) food environments. With common garden transplant experiments, we demonstrate that in HP populations evolution toward increased PGR was concomitant with an increase in relative phosphorus content. In contrast, LP populations evolved higher PGR without an increase in relative phosphorus content. We conclude that the GRH has the potential to predict microevolutionary change, but that its application is contingent on the environmental context. Our results highlight the potential of cryptic evolution in determining the performance response of populations to elemental limitation of their food resources.